Polymer electrolyte containing ionic aggregate, preparation method of polymer electrolyte and lithium metal battery

By using ionic aggregate-containing polymer electrolytes in lithium metal batteries, and using the combination of polyvinylidene fluoride, lithium salt, organic solvent and diluent, the low conductivity and stability problems of solid electrolytes in existing lithium metal batteries are solved, achieving efficient ion transport and excellent electrochemical performance.

CN119725713AActive Publication Date: 2025-03-28TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411933893.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The solid electrolytes of existing lithium metal batteries, especially polymer electrolytes represented by polyepoxy (PEO), are difficult to achieve large-scale application due to problems such as low room temperature ionic conductivity, low oxidation potential, and poor mechanical properties.

Method used

A polymer electrolyte containing ionic aggregates is used to form a composite solid electrolyte by combining polyvinylidene fluoride, lithium salt, organic solvent and diluent. The organic solvent dissociates the lithium salt to form a contact ion pair, and the diluent promotes the conversion of the contact ion pair into ion aggregates and is uniformly distributed in the polyvinylidene fluoride framework.

Benefits of technology

It significantly improves the ion conductivity of lithium metal batteries, realizes high-throughput ion transport, enhances electrochemical stability and cyclic stability, and especially shows excellent electrochemical cycling and safety performance in a wide temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725713A_ABST
    Figure CN119725713A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer electrolyte containing an ionic aggregate, a preparation method of the polymer electrolyte and a lithium metal battery. The polymer electrolyte containing the ion aggregate comprises polyvinylidene fluoride, a lithium salt, an organic solvent and a diluent, the organic solvent is used for dissociating the lithium salt to form a contact ion pair, the diluent does not have the capability of coordinating with lithium ions in the lithium salt and is used for promoting the contact ion pair to be converted into the ion aggregate, and the diluent is used for promoting the contact ion pair to be converted into the ion aggregate. And the ion aggregate is promoted to be uniformly distributed in a polyvinylidene fluoride skeleton. The polymer electrolyte disclosed by the invention can be well matched with a lithium metal negative electrode and a high-nickel ternary positive electrode, so that an assembled battery has excellent cycle stability in a wide temperature range of-30 DEG C to 60 DEG C, and has a relatively good application prospect in the field of batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a polymer electrolyte containing ion aggregates, a preparation method thereof and a lithium metal battery. Background Art

[0002] The development of new energy industries such as portable electronic products and electric vehicles has put forward higher requirements on the energy density and safety of lithium-ion batteries. Traditional lithium-ion batteries with graphite as negative electrode can no longer meet the development needs. Lithium metal negative electrode has a high theoretical capacity (3860mAh g –1 ) and low operating voltage (-3.04vs.SHE) and is considered to be the most promising negative electrode material and can be used in high energy density lithium metal batteries, such as ternary lithium metal batteries, lithium-sulfur batteries, etc.

[0003] However, there are many problems in the practical application of lithium metal. First, the uneven distribution of ions and electrons at the lithium metal / electrolyte interface leads to the growth of lithium dendrites, which can easily further puncture the diaphragm, leading to safety issues such as internal short circuits and the generation of dead lithium. Secondly, lithium metal has high reactivity with the electrolyte due to its very strong reducibility. Continuous side reactions lead to continuous loss of active lithium and increase in battery impedance, ultimately resulting in low battery coulombic efficiency and poor cycle stability. Therefore, developing solid electrolytes with high chemical stability and inherent high safety to replace liquid electrolytes is an effective way to achieve high-performance lithium metal batteries.

[0004] Solid polymer electrolytes have the advantages of good flexibility, good electrode contact, and low preparation cost, and are the most promising solid electrolyte system to be first industrialized. However, polymer electrolytes represented by poly(ethylene oxide) (PEO) are difficult to be applied on a large scale due to their low room temperature ionic conductivity, low oxidation potential, and poor mechanical properties. Although strategies such as adding inorganic fast ion conductor fillers, polymer molecular structure design, copolymerization, and cross-linking can effectively improve ionic conductivity, these methods still make it difficult to achieve polymer electrolytes that meet the requirements of practical lithium metal batteries.

[0005] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present invention, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0006] In order to make up for the deficiencies of the prior art, the present invention provides a polymer electrolyte containing ion aggregates, a preparation method thereof and a lithium metal battery.

[0007] The present invention adopts the following technical solution:

[0008] In a first aspect, a polymer electrolyte containing ion aggregates is provided, which includes polyvinylidene fluoride, a lithium salt, an organic solvent and a diluent, wherein the organic solvent is used to dissociate the lithium salt to form contact ion pairs, the diluent does not have the ability to coordinate with the lithium ions in the lithium salt, and the diluent is used to promote the conversion of the contact ion pairs into ion aggregates and promote the uniform distribution of the ion aggregates in the polyvinylidene fluoride skeleton.

[0009] In a second aspect, a method for preparing the polymer electrolyte according to the first aspect is provided, comprising the following steps:

[0010] S1, mixing polyvinylidene fluoride and lithium salt, and dissolving them in an organic solvent to obtain a uniform and transparent precursor solution;

[0011] S2, drying the precursor solution to obtain a polymer film containing an organic solvent;

[0012] S3, adding a diluent to the polymer membrane, so that the diluent is fully absorbed by the polymer membrane to obtain the polymer electrolyte.

[0013] In a third aspect, a lithium metal battery is provided, which comprises the polymer electrolyte containing ion aggregates as described in the first aspect.

[0014] The present invention has the following beneficial effects:

[0015] The polymer electrolyte of ion aggregates provided by the present invention is a composite solid electrolyte, including polyvinylidene fluoride, lithium salt, organic solvent and diluent, the organic solvent can dissociate lithium salt to form contact ion pairs, and the contact ion pairs are distributed in the polyvinylidene fluoride skeleton, thereby realizing ion transmission. The diluent does not have the ability to coordinate with lithium ions, and can promote the conversion of contact ion pairs into ion aggregates, and the diluent molecules are coated around the ion aggregates, effectively weakening the interaction between the ion aggregates and polyvinylidene fluoride, thereby greatly improving the ionic conductivity and realizing high-flux ion transport. The diluent promotes the uniform distribution of ion aggregates in the polyvinylidene fluoride skeleton, thereby realizing a uniform lithium ion transport channel. The diluent in the polymer electrolyte containing ion aggregates has high electrochemical stability and non-flammability, and the ion aggregates generate an interfacial intermediate phase rich in LiF at the interface between lithium metal and high-voltage positive electrode, effectively improving the cycle stability of high-voltage lithium metal batteries. The high-nickel ternary lithium metal battery assembled with the polymer electrolyte containing ion aggregates has excellent electrochemical cycle performance and safety performance in a wide temperature range of -30°C-60°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the thermogravimetric curve of the polymer film obtained in Example 1 of the present invention.

[0017] Figure 2 The figure is a comparison of ionic conductivity and activation energy between Example 1 of the present invention and Comparative Example 1.

[0018] Figure 3a It is the Raman spectrum of Comparative Example 1 of the present invention.

[0019] Figure 3b This is the Raman spectrum of Example 1 of the present invention.

[0020] Figure 4a This is the test result of the lithium ion migration number of Example 1 of the present invention.

[0021] Figure 4b It is the test result of the lithium ion migration number of comparative example 1 of the present invention.

[0022] Figure 5 It is a constant current charge and discharge test diagram of the lithium-lithium symmetric battery assembled in Example 1 of the present invention and Comparative Example 1.

[0023] Figure 6a This is a scanning electron microscope test image of the lithium-lithium symmetric battery assembled in Comparative Example 1 of the present invention after cycling.

[0024] Figure 6b This is a scanning electron microscope test image of the lithium-lithium symmetric battery assembled in Example 1 of the present invention after cycling.

[0025] Figure 7 This is a normal temperature (25°C) cycle test chart of the NCM811 lithium metal battery assembled in Example 1 of the present invention and Comparative Example 1.

[0026] Figure 8 This is a high temperature (60°C) cycle test diagram of the NCM811 lithium metal battery assembled in Example 1 of the present invention.

[0027] Fig. 9 This is a low temperature (-30°C) cycle performance test chart of the NCM811 lithium metal battery assembled in Example 1 of the present invention and Comparative Example 1.

[0028] Fig.10 This is a test chart of the cycle performance of the high energy density NCM811 lithium metal soft pack battery assembled in Example 2 of the present invention. DETAILED DESCRIPTION

[0029] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention. In the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other.

[0030] A specific embodiment of the present invention provides a polymer electrolyte containing ion aggregates, which includes polyvinylidene fluoride, lithium salt, organic solvent and diluent, wherein the organic solvent is used to dissociate the lithium salt to form contact ion pairs, the diluent does not have the ability to coordinate with the lithium ions in the lithium salt, and the diluent is used to promote the conversion of the contact ion pairs into ion aggregates and promote the uniform distribution of the ion aggregates in the polyvinylidene fluoride skeleton.

[0031] In some embodiments, the diluent is at least one of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), 2,2,2-trifluoroethyl ether, 1,1,1-trifluoro-2-[(2,2,2-trifluoroethoxy)methoxy]ethane, and fluorobenzene.

[0032] In some embodiments, the organic solvent is at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), tetraethylene glycol dimethyl ether (G4), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), N-methylpyrrolidone (NMP) and propylene carbonate (PC).

[0033] In some embodiments, the lithium salt is at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluorosulfonyl)imide (LiTFSI), and lithium difluorooxalatoborate (LiDFOB).

[0034] In some embodiments, the molar ratio of the organic solvent to the diluent is 1:(1-5).

[0035] In some embodiments, in the polymer electrolyte, the mass percentage of the organic solvent is 5% to 25%.

[0036] In some embodiments, the mass ratio of polyvinylidene fluoride to lithium salt is (1-3):1.

[0037] In some embodiments, the polymer electrolyte is in a film shape with a thickness of 80-100 μm.

[0038] The specific embodiment of the present invention also provides a method for preparing the polymer electrolyte, which comprises the following steps:

[0039] S1, mixing polyvinylidene fluoride and lithium salt, and dissolving them in an organic solvent to obtain a uniform and transparent precursor solution;

[0040] Preferably, in this step S1, the mass ratio of polyvinylidene fluoride (PVDF) and lithium salt is (1-3): 1. Polyvinylidene fluoride and lithium salt are added to an organic solvent and stirred for 6-8 hours to completely dissolve the polyvinylidene fluoride and lithium salt in the organic solvent to form a uniform and transparent precursor solution.

[0041] S2, drying the precursor solution to obtain a polymer membrane containing an organic solvent (called a PVDF polymer electrolyte membrane);

[0042] Preferably, in this step S2, the precursor solution obtained in step S1 can be poured into a glass dish and placed in a forced air oven for drying at 55°C for 20 to 24 hours to obtain a PVDF polymer electrolyte membrane with a thickness of 80 to 100 μm, wherein the mass proportion of the organic solvent in the PVDF polymer electrolyte membrane is 5% to 25%, and the organic solvent can dissociate the lithium salt to form contact ion pairs.

[0043] After step S2, the polymer film presents a porous spherulite structure, and the contact ion pairs are gathered in the surface part of the spherulites, and are unevenly distributed as a whole.

[0044] S3. Adding a diluent (such as dripping it) to the polymer film, so that it is fully absorbed by the polymer film, to obtain the polymer electrolyte. The polymer electrolyte is in a film shape with a thickness of 80 to 100 μm. In the polymer electrolyte, the mass percentage of the organic solvent is also 5% to 25%.

[0045] In this step S3, the introduction of the diluent can promote the uniform distribution of ion aggregates in the polyvinylidene fluoride skeleton, thereby realizing a uniform lithium ion transport channel; the diluent does not have the ability to coordinate with lithium ions, and can promote the conversion of contact ion pairs into ion aggregates, and the diluent molecules are coated around the ion aggregates, effectively weakening the interaction between the ion aggregates and PVDF, thereby greatly improving the ionic conductivity and realizing high-flux ion transport. The diluent in the polymer electrolyte containing ion aggregates has high electrochemical stability and non-flammability, and the ion aggregates generate a LiF-rich interphase at the interface of lithium metal and high-voltage positive electrode, effectively improving the cycle stability of high-voltage lithium metal batteries.

[0046] The specific embodiment of the present invention also provides a lithium metal battery, which includes the polymer electrolyte containing ion aggregates. Specifically, the lithium metal battery includes a polymer electrolyte containing ion aggregates, a lithium metal negative electrode and a positive electrode, the polymer electrolyte containing ion aggregates is placed between the lithium metal negative electrode and the positive electrode, and the active material in the positive electrode includes one of lithium cobalt oxide, a ternary positive electrode material, and lithium-rich manganese.

[0047] The scheme of the present invention will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present invention and cannot be understood as limiting the present invention. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0048] Example 1

[0049] This embodiment provides a method for preparing a polymer electrolyte containing ion aggregates and assembling a solid-state lithium metal battery, comprising at least the following steps:

[0050] (1) Weigh 405 mg of polyvinylidene fluoride (PVDF) powder with a molecular weight of 600,000 and 270 mg of lithium bis(fluorosulfonyl)imide (LIFSI) and dissolve them in 15 mL of N,N-dimethylformamide (DMF), and stir at room temperature for 8 hours until PVDF and LiFSI are completely dissolved to obtain a uniform and transparent precursor solution;

[0051] (2) The precursor solution obtained in step (1) was poured into a glass culture dish and placed in a 55° C. forced air oven for drying for 24 hours to obtain a PVDF polymer electrolyte membrane, which was punched into discs with a diameter of 19 mm and stored dry in an inert atmosphere until use.

[0052] (3) First, weigh 100 mg of PVDF (binder) and place it in a stirring bottle, add 2 mL of N-methylpyrrolidone (NMP), and stir on a magnetic stirrer for 2 hours until PVDF is completely dissolved to obtain a uniform and transparent PVDF binder solution. Then, add 100 mg of SuperP (conductive carbon black) and 800 mg of ternary nickel-cobalt-manganese (NCM811) active material to the binder solution, and stir on a high-speed defoamer at 1200 rpm / min for 15 minutes to obtain a positive electrode slurry.

[0053] (4) The positive electrode slurry obtained in step (3) is coated on aluminum foil, dried in a forced air oven at 80°C for more than 6 hours, cut into discs with a diameter of 12 mm to obtain NCM811 positive electrode sheets, placed in a vacuum oven at 120°C for 1 hour, and stored in an inert atmosphere in a glove box for future use.

[0054] (5) 8 μL of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) was added to the polymer membrane obtained in step (2) to obtain a polymer electrolyte membrane containing ion aggregates with a thickness of 85 μm.

[0055] (6) Assembling the NCM811 positive electrode sheet prepared in step (4), the polymer electrolyte membrane containing ion aggregates prepared in step (5), and lithium metal to obtain a lithium metal button battery.

[0056] Example 2

[0057] The difference between Example 2 and Example 1 is that the cutting size of the PVDF polymer electrolyte membrane in step (2) is replaced with 4.0 cm*4.5 cm, the cutting size of the positive electrode in step (3) is replaced with 3.5 cm*4.0 cm, the amount of TTE added in step (5) is replaced with 50 μL, the lithium metal button battery is replaced with a soft-pack battery, and the remaining steps are the same as Example 1.

[0058] Example 3

[0059] The difference between Example 3 and Example 1 is that the DMF solvent is replaced by N,N-dimethylacetamide, and the remaining steps are the same as Example 1.

[0060] Example 4

[0061] The difference between Example 4 and Example 1 is that the DMF solvent is replaced by diethylene glycol dimethyl ether, and the remaining steps are the same as Example 1.

[0062] Example 5

[0063] The difference between Example 5 and Example 1 is that the DMF solvent is replaced by propylene carbonate, and the remaining steps are the same as Example 1.

[0064] Example 6

[0065] The difference between Example 6 and Example 1 is that the NCM811 positive electrode active material is replaced with a lithium-rich manganese positive electrode active material, and the remaining steps are the same as those of Example 1.

[0066] Example 7

[0067] The difference between Example 7 and Example 1 is that the NCM811 positive electrode active material is replaced by LiCoO 2 The remaining steps are the same as those in Example 1.

[0068] Example 8

[0069] The difference between Example 8 and Example 1 is that the NCM811 positive electrode active material is replaced by LiCoO 2 The active substance and the diluent were replaced by 1,1,1-trifluoro-2-[(2,2,2-trifluoroethoxy)methoxy]ethane from TTE, and the remaining steps were the same as those in Example 1.

[0070] Example 9

[0071] The difference between Example 9 and Example 1 is that the NCM811 positive electrode active material is replaced by LiCoO 2The active substance and the diluent were replaced by fluorobenzene from TTE, and the remaining steps were the same as those in Example 1.

[0072] Comparative Example 1

[0073] The difference between Comparative Example 1 and Example 1 is that no TTE diluent is added to the prepared PVDF polymer electrolyte membrane, and the remaining steps are the same as those of Example 1.

[0074] The present invention conducted a thermogravimetric analysis of the PVDF polymer electrolyte membrane prepared in step (2) of Example 1 under a nitrogen atmosphere. Figure 1 It was found that the content of DMF solvent in the PVDF polymer electrolyte membrane was 18 wt %.

[0075] The present invention compares the ionic conductivity and activation energy of the polymer electrolyte containing ion aggregates prepared in Example 1 at different temperatures with those of Comparative Example 1. Figure 2 ,The results show that the addition of diluent can effectively improve the ionic conductivity of the electrolyte and reduce the activation energy by homogenizing the distribution of lithium ion aggregates in the PVDF skeleton and weakening the interaction between the ion aggregates and PVDF.

[0076] The present invention studies the solvation structure of the electrolyte prepared in Example 1 and Comparative Example 1 by Raman spectroscopy. Figure 3a and 3b The results show that the addition of diluent can transform the contact ion pairs in the PVDF polymer electrolyte membrane into ion aggregates, thereby effectively improving the ability of lithium ion complexes to build stable interfaces at the positive and negative electrode interfaces. Figure 4a and 4b The solvation structure dominated by ion aggregates makes the polymer electrolyte containing ion aggregates in Example 1 show a lithium ion transference number as high as 0.5.

[0077] The present invention evaluates the stability of the lithium metal negative electrode by assembling a lithium-lithium symmetric battery with the electrolyte prepared in Example 1 and Comparative Example 1. Figure 5 , at 0.5 mA cm – 2 The current density and 0.5 mAh cm – 2 Under the condition of the deposition amount of 1.5 wt %, the polymer electrolyte containing ion aggregates prepared in Example 1 has a cycle life of up to 4000 hours, while the PVDF polymer electrolyte membrane without adding diluent fails after only 200 hours of cycle. Furthermore, the two symmetrical batteries were disassembled and the surface morphology of lithium metal was characterized by scanning electron microscopy. Figure 6a and 6bThe symmetrical battery assembled using the electrolyte in Example 1 has a dense and smooth lithium deposition morphology, while the symmetrical battery assembled using the electrolyte in Comparative Example 1 has more accumulation of side reaction products and lithium dendrite formation. The above results show that the uniform lithium ion flow brought by the introduction of the diluent and the regulation of the solvation structure effectively inhibit the side reaction between the electrolyte and lithium metal and the growth of lithium dendrites.

[0078] The present invention tests the cycle performance of the NCM811 lithium metal battery assembled in Example 1 and Comparative Example 1 at room temperature. Figure 7 The NCM811 lithium metal battery in Example 1 can operate stably for 1000 times at room temperature and has a capacity retention rate of 70%, while the comparative example 1 has a short circuit failure within 200 cycles.

[0079] The present invention tests the cycle performance of the NCM811 lithium metal battery in Example 1 at 60°C. Figure 8 The NCM811 lithium metal battery in Example 1 can stably operate at a high rate of 5C for 300 times at 60°C, indicating the applicability of the electrolyte and battery of the present invention in high-temperature usage scenarios.

[0080] The present invention tests the cycle performance of the NCM811 lithium metal battery in Example 1 at -30°C. Fig. 9 The NCM811 lithium metal battery in Example 1 can operate stably for 400 times at -30°C, indicating the applicability of the electrolyte and battery of the present invention in low-temperature usage scenarios.

[0081] The present invention tests the cycle performance of the high energy density NCM811 lithium metal soft pack battery in Example 2 at room temperature. Fig.10 , the soft pack in Example 2 can stably operate 450 times with a capacity retention rate of 80%, indicating the applicability of the electrolyte of the present invention in high energy density lithium metal soft pack batteries.

[0082] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.

Claims

1. A polymer electrolyte containing ion aggregates, characterized in that: The invention comprises polyvinylidene fluoride, lithium salt, organic solvent and diluent, wherein the organic solvent is used for dissociating the lithium salt to form contact ion pairs, the diluent does not have the ability to coordinate with the lithium ions in the lithium salt, and the diluent is used for promoting the conversion of the contact ion pairs into ion aggregates and promoting the uniform distribution of the ion aggregates in the polyvinylidene fluoride skeleton.

2. The polymer electrolyte according to claim 1, characterized in that The diluent is at least one of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), 2,2,2-trifluoroethyl ether, 1,1,1-trifluoro-2-[(2,2,2-trifluoroethoxy)methoxy]ethane, and fluorobenzene.

3. The polymer electrolyte according to claim 1, characterized in that The organic solvent is at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), tetraethylene glycol dimethyl ether (G4), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), N-methylpyrrolidone (NMP) and propylene carbonate (PC).

4. The polymer electrolyte according to claim 1, characterized in that The lithium salt is at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluorosulfonyl)imide (LiTFSI), and lithium difluorooxalatoborate (LiDFOB).

5. The polymer electrolyte according to claim 1, characterized in that The molar ratio of the organic solvent to the diluent is 1:(1-5).

6. The polymer electrolyte according to claim 1, characterized in that In the polymer electrolyte, the mass percentage of the organic solvent is 5% to 25%.

7. The polymer electrolyte according to claim 1, characterized in that The mass ratio of polyvinylidene fluoride and lithium salt is (1-3):

1.

8. The polymer electrolyte according to claim 1, characterized in that The polymer electrolyte is in a film shape with a thickness of 80-100 μm.

9. A method for preparing a polymer electrolyte according to any one of claims 1 to 8, characterized in that: The steps include: S1, mixing polyvinylidene fluoride and lithium salt, and dissolving them in an organic solvent to obtain a uniform and transparent precursor solution; S2, drying the precursor solution to obtain a polymer film containing an organic solvent; S3, adding a diluent to the polymer membrane, so that the diluent is fully absorbed by the polymer membrane to obtain the polymer electrolyte.

10. A lithium metal battery, characterized in that: A polymer electrolyte comprising the ion aggregate according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of polymer electrolyte taking cellulose as additive

    CN111490288A

  • Composite solid electrolyte, preparation method thereof and lithium metal battery

    CN116454370A

  • In-situ polymerization solid-state electrolyte precursor solution and solid-state battery

    CN118063692A

  • Electrolytes for lithium-ion batteries operating at extreme conditions

    US20240405286A1

  • Solid-Liquid Composite Electrolyte Including Sulfide-based Solid Electrolyte and High-kosmotropicity Salt-containing Liquid Electrolyte, and Semi-solid-state Rechargeable Batteries

    US20240413384A1